Thromboprophylaxis in Surgical and Medical Patients - Bozzato, Silvia; Galli, Luca; Ageno, Walter (Seminars in Respiratory and Critical Care Medicine, 2012)
Venous thromboembolism (VTE) remains the most common preventable cause of death in hospitalized patients. There is much evidence to show the efficacy of prophylactic strategies to prevent VTE in at-risk hospitalized patients. For example, pharmacological prophylaxis reduces the risk of pulmonary embolism by 75% in general surgical patients and by 57% in medical patients. Thus international guidelines strongly recommend effective preventive strategies for all hospitalized patients defined as moderate to high risk for VTE. Effective pharmacological thromboprophylaxis includes low-dose unfractionated heparin (UFH), low molecular weight heparin (LMWH), fondaparinux, and warfarin. Mechanical prophylaxis with graduated compression stockings and intermittent pneumatic compression is also recommended as an alternative or in combination with pharmacological prophylaxis. Although the volume of evidence supporting the use of thromboprophylaxis is growing, the number of patients receiving adequate prophylaxis is not. Several studies have shown that nearly half of the patients undergoing major surgery or hospitalized for medical illnesses do not receive appropriate antithrombotic prophylaxis. Reducing the discrepancy between evidence-based recommendations and clinical practice seems to be a cost-effective goal. Developing and promoting local protocols and educational activities to encourage prophylaxis in daily clinical practice may be effective. New oral anticoagulant drugs with potentially favorable pharmacokinetic and pharmacodynamic characteristics have been developed. After the positive results of phase 3 clinical trials, some of these drugs have been approved for clinical use in the prevention of VTE in the high-risk setting of major orthopedic surgery. These agents include the direct thrombin inhibitor dabigatran etexilate and the direct factor Xa inhibitors rivaroxaban and apixaban.
Keywords: deep venous thrombosis; thromboprophylaxis; heparin; anticoagulation; fondaparinux; warfarin